Genetic Relationship Analysis of Shallot Clones (Allium cepa L. var. aggregatum) from Sumbawa Island Using Simple Sequence Repeat (SSR) Markers - Kurniawan Putra; Marselianti; Gilang Anugrah Romadhan; Adelia Elviantari; Azril Al Ghazali (Wakil Rektor 3, Direktorat Riset, Publikasi dan Inovasi, Universitas Teknologi Sumbawa, 2026)
Shallot (Allium cepa L. var. aggregatum) is a strategic horticultural commodity in Indonesia, with West Nusa Tenggara Province serving as one of the major production centers; however, shallot production on Sumbawa Island has declined significantly in recent years. This decline is driven by outbreaks of Fusarium wilt caused by Fusarium sp., which result in substantial yield losses, while current control strategies that rely heavily on fungicide application are considered ineffective and unsustainable. These challenges are further exacerbated by the use of planting material derived from previous harvests without genetic resistance selection, as well as the absence of shallot breeding programs on Sumbawa Island. In this context, the identification of genetic relatedness and diversity is a fundamental step in understanding the genetic structure of shallot populations, which can be accurately assessed using Simple Sequence Repeat (SSR) molecular markers. Therefore, this study aimed to identify the genetic relationship and diversity of shallot clones using SSR markers. The research methods included shallot sampling, genomic DNA isolation, primer screening for SSR-PCR, SSR-based PCR amplification, and data analysis. Shallot cultivation in Sumbawa Regency and West Sumbawa Regency is distributed across the eastern part of Sumbawa Regency and the western part of West Sumbawa Regency, encompassing ten cultivation sites located in several sub-districts. Molecular analysis using simple sequence repeat (SSR) markers revealed that only nine out of fourteen primer pairs were polymorphic, with all samples exhibiting identical DNA banding patterns, indicating low genetic diversity likely resulting from the use of a common parental seed source.